K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 7 2015

x^3+5x^2+8x+4=0

x^3+x^2+4x^2+4x+4x+4=0

x^2(x+1)+4x(x+1)+4(x+1)=0

(x+1)(x^2+4x+4)=0

x+1=0 =>x=-1

x^2+4x+4=0

x^2+2x+2x+4=0

x(x+2)+2(x+2)=0

(x+2)^2=0

x=-2

Vậy x=-2,x=-1

 

29 tháng 7 2016

x^5 -x^3 -x^2 +1=0

x^3(x^2 -1 )-(x^2-1)=0

(x-1)(x^2+x+1)(x-1)(x+1)=0

(x-1)^2(x+1)(x^2+x+1)=0

=> x=1;x=-1

29 tháng 7 2016

x^3- 5x^2+ 8x- 4= x^3- x^2- 4x^2+ 4x+ 4x- 4

                       = x^2(x-1)- 4x(x-1)+4(x-1)

                       = (x-1)(x^2-4x+4)

                       = (x-1)(x-1)^2

                       =(x-1)^3

5 tháng 8 2016

1,

<=> \(\left(x-1\right)\left(x-2\right)^2=0\)

=> x=1 hoặc x=2

2, 

<=>\(\left(x+1\right)\left(2x^2-3x+6\right)\)=0

=> x=-1

18 tháng 7 2017

1.

<=> ( x -1 ) ( x - 2 ) 2 = 0

=> x = 1 hoặc x = 2

2.

<=> ( x + 1 ) ( 2x2 - 3x + 6 ) = 0

=> x = -1

a, 4x2 - 49 = 0

⇔⇔ (2x)2 - 72 = 0

⇔⇔ (2x - 7)(2x + 7) = 0

⇔{2x−7=02x+7=0⇔⎧⎪ ⎪⎨⎪ ⎪⎩x=72x=−72⇔{2x−7=02x+7=0⇔{x=72x=−72

b, x2 + 36 = 12x

⇔⇔ x2 + 36 - 12x = 0

⇔⇔ x2 - 2.x.6 + 62 = 0

⇔⇔ (x - 6)2 = 0

⇔⇔ x = 6

e, (x - 2)2 - 16 = 0

⇔⇔ (x - 2)2 - 42 = 0

⇔⇔ (x - 2 - 4)(x - 2 + 4) = 0

⇔⇔ (x - 6)(x + 2) = 0

⇔{x−6=0x+2=0⇔{x=6x=−2⇔{x−6=0x+2=0⇔{x=6x=−2

f, x2 - 5x -14 = 0

⇔⇔ x2 + 2x - 7x -14 = 0

⇔⇔ x(x + 2) - 7(x + 2) = 0

⇔⇔ (x + 2)(x - 7) = 0

⇔{x+2=0x−7=0⇔{x=−2x=7

23 tháng 8 2016

làm dùm bn 1 bài thôi

=( 2x -3 +x+5)(2x-3-x-5)=0

3x + 2=0

x = -2/3

x-8 =0

x = 8

31 tháng 8 2016

     x(2x-7)-4x+14=0

=> x(2x-7)-2(2x-7)=0

=> (x-2)(2x-7)=0

=> x=2 hoặc x=7/2

a: \(x^3-5x^2+8x-4=0\)

\(\Leftrightarrow x^3-x^2-4x^2+4x+4x-4=0\)

\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\)

hay \(x\in\left\{1;2\right\}\)

b: \(2x^3-x^2+3x+6=0\)

\(\Leftrightarrow2x^3+2x^2-3x^2-3x+6x+6=0\)

\(\Leftrightarrow\left(x+1\right)\left(2x^2-3x+6\right)=0\)

=>x+1=0

hay x=-1